2021
DOI: 10.3390/ijms22073596
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Prevents Oxidative Stress Effects on FSHR, PAPP, and CYP19A1 Gene Expression in Cultured Human Granulosa-Lutein Cells

Abstract: Regulation of oxidative stress (OS) is important to prevent damage to female reproductive physiology. While normal OS levels may have a regulatory role, high OS levels may negatively affect vital processes such as folliculogenesis or embryogenesis. The aim of this work was to study OS induced by glucose, a reactive oxygen species generator, or peroxynitrite, a reactive nitrogen species generator, in cultured human granulosa-lutein (hGL) cells from oocyte donors, analyzing expression of genes involved in oocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Analysis of gene expression in hGL cells treated with glucose showed no variation in sirtuins’ gene expression ( Figure 3 B, Figure 4 B and Figure 5 B), even though previous studies demonstrated an increased ROS/RNS by the addition of glucose to culture medium [ 38 ]. An increase in DNA damage and in the number of dead cells was observed ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Analysis of gene expression in hGL cells treated with glucose showed no variation in sirtuins’ gene expression ( Figure 3 B, Figure 4 B and Figure 5 B), even though previous studies demonstrated an increased ROS/RNS by the addition of glucose to culture medium [ 38 ]. An increase in DNA damage and in the number of dead cells was observed ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 82%
“…The addition of OS inductors (glucose or peroxynitrite) to cultured hGL cells increased DNA damage and the percentage of dead cells compared to control, most prominently under peroxynitrite treatment ( Figure 1 A). Previous studies from our laboratory showed that higher ROS/RNS levels in cells treated with glucose or peroxynitrite [ 38 ] increased OS levels, leading to DNA damage and cell death. In this article, we report that the addition of antioxidants (celastrol or melatonin) to culture medium elicits an increase in the amount of high/medium level of 8-OHdG staining (a measure of DNA damage) compared to the amount found in control cells, but in contrast, we found an increase in the total number of surviving cells ( Figure 1 B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence demonstrates that age-related GC dysfunction contributes to decreased oocyte quality. Excessive ROS production also causes the downregulation of FSH-receptor expression in GCs, resulting in an adverse response to FSH and subsequent impaired follicle development with age (Martín-Ramírez et al, 2021). Furthermore, advanced glycation end products (AGEs) lead to protein damage and increases in inflammatory reactions, eventually inducing ovarian function decline (Lliberos et al, 2020;Pertynska-Marczewska and Diamanti-Kandarakis, 2017).…”
Section: The Molecular Mechanisms Underlying Age-associatedmentioning
confidence: 99%
“…Table 1 summarizes the mechanisms and effects of some drugs on OS in GCs. Celastrol [160,172] Human granulosa-lutein cells Induces SIRT7 gene expression. Improves cell viability.…”
Section: Growth Hormonementioning
confidence: 99%